FACTORS ASSOCIATED WITH THE OCCURRENCE OF VAGINAL DISCHARGE AMONG FEMALE STUDENTS LIVING IN THE MIDWIFERY STUDENT DORMITORY - Utin Siti Chandra Sari; Diani Magasida; Ratna Indah Kartikasari; Ade Fitriana (Jurnal Kebidanan Khatulistiwa, 2026)
Background: Adolescence is a transitional period characterized by significant physical, biological, and psychological changes. Failure to adapt to these changes may lead to various reproductive health problems, including vaginal discharge. A preliminary study conducted at the Midwifery Student Dormitory of Pontianak Health Polytechnic, Ministry of Health, Indonesia, revealed that six out of ten students experienced vaginal discharge. Objective: This study aimed to determine the association between personal hygiene practices and the use of feminine hygiene products with the occurrence of vaginal discharge among female students. Methods: This study employed a descriptive analytical design using a cross-sectional approach. The study population consisted of all female students residing in the Midwifery Student Dormitory of Pontianak Health Polytechnic, Ministry of Health, Indonesia, in 2025. A total of 145 respondents were recruited using a total sampling technique. Data were collected using a structured questionnaire and analyzed through univariate and bivariate statistical analyses. Results: The findings demonstrated no statistically significant association between personal hygiene practices and the occurrence of vaginal discharge. Likewise, no significant relationship was found between the use of feminine hygiene products and the occurrence of vaginal discharge among the respondents. Conclusion: Although no significant associations were identified, reproductive health education remains essential for improving awareness and promoting appropriate personal hygiene practices to maintain female reproductive health.